Pengaruh Persepsi Profesi dan Kesadaran Etis Terhadap Komitmen Profesi Akuntan Publik : Studi Auditor Pada Kantor Akuntan Publik Wilayah Surabaya - Achmad Nur Fauzan Aprilianto (Universitas 45 Surabaya, 2024)
A number of codes of ethics regulate how members of the public accounting profession are expected to behave. The problem of ethical violations that occur in the auditor environment is one of the things that needs to be considered, because it causes public trust in the public accounting profession to decline. The purpose of the written research is to find out: (1) how professional perception influences the level of commitment of the public accounting profession. (2) How ethical awareness influences the dedication of the public accounting profession. The written research is a survey research by distributing questionnaires to the sample directly. Participants in the written research were all auditors working at the Surabaya Public Accounting Office. The sample selected was 40 auditors with a simple sampling technique. Multiple regression analysis was used in the data analysis technique. The conclusion of the written research shows: (1) The commitment of the public accounting profession is significantly and positively influenced by public perception. The auditor's ethical awareness and dedication to the public accounting profession are positively correlated. The implications of the written research are in improving the skills, dedication, and professionalism of auditors working in public accounting offices so that they can provide services expected by the general public. This can be achieved by increasing knowledge in this field, which will influence the perception of the auditor profession. This can be done through training and discussions on the field of auditing.